Targeting IL-34/MCSF-1R Axis in Colon Cancer - Monteleone, Giovanni; Maresca, Claudia; Colella, Marco; Pacifico, Teresa; Congiu, Daniele; Troncone, Edoardo; Marafini, Irene (Frontiers in Immunology, 2022)
Colorectal carcinoma (CRC) is one of the most common neoplasias in the Western world and it is still one of the most deadly cancers worldwide mainly due to the fact that metastatic CRC is not responsive to current pharmacologic treatment. Identification of pathways that sustain CRC cell behaviour could help develop effective therapeutic compounds. A large body of evidence indicates that colon carcinogenesis is a dynamic process in which multiple cell types present in the tumor microenvironment either stimulate or suppress CRC cell growth, survival, and diffusion mainly via the production of cytokines. Interleukin-34 (IL-34), a cytokine initially known for its ability to regulate monocyte/macrophage survival and function, is highly produced in human CRC by both cancer cells and non-tumoral cells. IL-34 function is mainly mediated by interaction with the macrophage colony-stimulating factor-1 receptor (MCSF-1R), which is also over-expressed by CRC cells as well as by tumour-associated macrophages (TAMs) and cancer-associated fibroblasts. IL-34-driven MCSF-1R activation triggers several pro-tumoral functions in the colon. In this article, we review the current understanding of the involvement of IL-34 and its receptor in CRC, with particular attention to the available evidence about the IL-34/MCSF-1R axis-mediated regulation of TAMs and the role of IL-34 and MCSF-1R in promoting cancer resistance to chemotherapy and immunotherapy.